José Francisco Alegría. Gagá y Vudú en la República Dominicana. Santo Domingo-Puerto Rico. Ediciones el Chango Prieto, 1993 - Andújar, Carlos (Universidad Autónoma de Santo Domingo (UASD), 1996)
No precisa de un resumen.